تأثير الخلائط العلفية في نوعية الدريس تحت ظروف الساحل السوري (Latakia University Journal -Biological Sciences Series, 2014)
نُفذّ البحث في مزرعة بوقا التابعة لكلّيّة الزراعة، جامعة تشرين خلال الموسمين الزراعيين 2008 و2009 باستخدام أربعة محاصيل علفية هي: التريتكالي، والشعير، والبيقية، والجلبان بزراعة كلّ منها على نحو منفردٍ وبزراعتها معاً في خلائط ثنائية وثلاثية ورباعية، وحضّر الدريس بالتجفيف الطبيعي وقدّر محتواه من البروتين الخام والرماد والألياف الخام في مخابر جامعة تشرين. تفوقت المحاصيل البقولية في محتواها من البروتين الخام ومن الرماد سواء بزراعتها منفردة أو في خلائط معاً مثل مخلوط البيقية والجلبان، أما المحاصيل النجيلية فقد تفوقت على البقوليات بمحتواها من الألياف الخام. ولوحظت أعلى نسبة بروتين خام في دريس البيقية (15.37% في مرحلة التبرعم). وكانت أعلى نسبة ألياف خام في التريتكالي (29.91% عند طرد السنابل).This study was carried out in Bouka farmland/Faculty of Agriclture/Tishreen University/Syria during the growing season (2008-2009). Four forage crops (triticale, barley, common vetch, and peavine grass) were used in the study, each of which was planted individually and together in mixtures of two, three and four crops. The hay was naturally dried and its content of crude protein, ash, crude fiber was estimated in the laboratories of Tishreen University. Leguminous crops (planted both individually and in mixtures like peas and vetch mixtures) were superior in the content of crude protein and ash, whereas the cereal crops surpassed leguminous crops in their content of crude fiber. A higher percentage of crude protein was observed in hay vetch (15.37% in the budding stage). The highest percentage of crude fiber was found in Triticale (29.91% at the expulsion of the ears).